Effects of liquid water on transport in the catalyst layer of proton exchange membrane fuel cells - Min, Ting; Zhou, Qiang (Frontiers in Energy Research, 2023)
Nanoscale structures of catalyst layers (CLs) of proton exchange membrane fuel cells are reconstructed with pores, carbon, Pt particles and ionomer fully resolved. Distributions of liquid water with different saturation and wettability within nanoscale structures are simulated by the lattice Boltzmann method. Pore-scale modelling of oxygen reactive transport in the nanoscale structures is implemented, with oxygen diffusion in pores and ionomer as well as electrochemical reaction at Pt surface considered. Effects of liquid water on pore size distribution, electrochemical area and oxygen concentration distribution are discussed. Liquid water in hydrophilic CL tends to form film covering on the reactive sites, while that in hydrophobic CL forms droplet preferentially occupying large pores. For hydrophilic case local transport resistance increases significantly under a low saturation, while for hydrophobic case remarkable increase of the local transport resistance can only be found after liquid water saturation higher than 0.8. Finally, the conjecture that liquid water in pores with size smaller than a threshold pore size can conduct proton is considered. Different values of threshold pore size are studied. The results show that when the threshold value is greater than 10 nm, the local transport resistance will decrease as the liquid water saturation increases, which means the optimizing strategy of CL needs to carefully consider the effects of liquid water.